ARK 2018: AWI airborne ultra-wideband microwave radar data at and upstream of 79°N Glacier, northeast Greenland Ice Sheet (RESURV 79 Project) - Angelika Humbert; Tobias Binder; Daniel Steinhage; Veit Helm (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWI ultra-wideband microwave radar (UWBM) during the Arctic season of 2018. The profiles extend across the Greenland Ice Sheet over and upstream of 79°N Glacier (Nioghalvfjerdsbræ; northeast Greenland). Furthermore, one flight extends over sea ice northeast of the Greenland Ice Sheet. The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams. For every profile we provide four radar products (img_01, img_02, img_03, img_04), which correspond to the four polarizations (VV, VH, HH, HV).